The sequence satisfies and for .
Evaluate .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Relevant wiki: Fibonacci Sequence
We note that
\(\begin{array} {} x_0 = 1 = \dfrac 11 & = \dfrac {F_2}{F_1} \\ x_1 =1 + \dfrac 1{1+1} = \dfrac 32 & = \dfrac {F_4}{F_3} \\ x_2 =1 + \dfrac {\frac 32}{1+\frac 32} = \dfrac 85 & = \dfrac {F_6}{F_5} \end{array} \)
The first few x n implies the claim that x n = F 2 n + 1 F 2 n + 2 , where F n is the n th Fibonacci number. Let us prove by induction that the claim is true for all n ≥ 0 . Assuming the claim is true for n , then:
x n + 1 = 1 + 1 + x n x n = 1 + 1 + F 2 n + 1 F 2 n + 2 F 2 n + 1 F 2 n + 2 = 1 + F 2 n + 1 + F 2 n + 2 F 2 n + 2 = 1 + F 2 n + 3 F 2 n + 2 = F 2 n + 3 F 2 n + 3 + F 2 n + 2 = F 2 n + 3 F 2 n + 4
Therefore, the claim is also true for n + 1 and hence true for all n ≥ 0 . Then we have n → ∞ lim x n = n → ∞ lim F 2 n + 3 F 2 n + 4 = φ ≈ 1 . 6 1 8 , where φ denotes the golden ratio.